Evaluation of the suitability of marine tourism in the Mandeh Archipelago, West Sumatra - Iswandi Umar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Indonesia has a huge potential in the development of marine tourism, because it has many islands and very beautiful coastal areas. The Mandeh area has enormous potential in developing marine tourism, due to its beautiful coastal areas and islands. The purpose of this study was to evaluate land suitability and determine constraints for the development of marine tourism in the Mandeh area. To determine the evaluation of land suitability using the Geographical Information System (GIS) method using ten indicators, namely: depth, beach type, beach width, basic material, current velocity, coastal independence, beach brightness, land use, hazardous biota, and availability of fresh water. Furthermore, to determine the constraints using the Interpretative Structural Modeling (ISM) method, the ISM method involves stakeholders from tourism experts, community leaders, tourism businesses, local governments. The results of research on the evaluation of the land suitability of marine tourism in the Mandeh area are mostly or about 35% very suitable (S1) for marine tourism, while the unsuitable area (N) is only 20% of the total area. Based on the analysis of the obstacles to developing marine tourism in the Mandeh area, namely the lack of investment capital and professional personnel in the development of marine tourism.